Functional relevance of resistance training-induced neuroplasticity in health and disease. (March 2021) - Hortobágyi, Tibor; Granacher, Urs; Fernandez-del-Olmo, Miguel; Howatson, Glyn; Manca, Andrea; Deriu, Franca; Taube, Wolfgang; Gruber, Markus; Márquez, Gonzalo; Lundbye-Jensen, Jesper; Colomer-Poveda, David
Highlights: Short-term resistance training (RT) increases maximal voluntary force and motor performance in health and disease. Neuroplastic changes accompany such improvements. However, the induced neuroplasticity and improved motor performance tend to be uncorrelated. Thus, the functional role of neuroplasticity in improved motor function after RT is unclear. Network causal mediation analyses could identify functional role of neuroplasticity in improving motor function after RT in health and disease. Abstract: Repetitive, monotonic, and effortful voluntary muscle contractions performed for just a few weeks, i.e., resistance training, can substantially increase maximal voluntary force in the practiced task and can also increase gross motor performance. The increase in motor performance is often accompanied by neuroplastic adaptations in the central nervous system. While historical data assigned functional relevance to such adaptations induced by resistance training, this claim has not yet been systematically and critically examined in the context of motor performance across the lifespan in health and disease. A review of muscle activation, brain and peripheral nerve stimulation, and imaging data revealed that increases in motor performance and neuroplasticity tend to be uncoupled, making a mechanistic link between neuroplasticity and motor performance inconclusive. We recommend new approaches, including causal mediation analytical and hypothesis-driven models to substantiate the functional relevance of resistance training-induced neuroplasticity in the improvements of gross motor function across the lifespan in health and disease.